Physics of Biological Membranes (Cham : Springer International Publishing, 2018)
This book mainly focuses on key aspects of biomembranes that have emerged over the past 15 years. It covers static and dynamic descriptions, as well as modeling for membrane organization and shape at the local and global (at the cell level) scale. It also discusses several new developments in non-equilibrium aspects that have not yet been covered elsewhere. Biological membranes are the seat of interactions between cells and the rest of the world, and internally, they are at the core of complex dynamic reorganizations and chemical reactions. Despite the long tradition of membrane research in biophysics, the physics of cell membranes as well as of biomimetic or synthetic membranes is a rapidly developing field. Though successful books have already been published on this topic over the past decades, none include the most recent advances. Additionally, in this domain, the traditional distinction between biological and physical approaches tends to blur. This book gathers the most recent advances in this area, and will benefit biologists and physicists alike. .
Part 1. Introduction -- 1. Understanding Membranes and Vesicles: A Personal Recollection of the Last Two Decades -- 2. Advanced Concepts and Perspectives of Membrane Physics -- Part 2: Membranes by the Numbers -- 3. Membranes by the Numbers -- Part 3: Spatial Heterogeneities in Biomembranes -- 4. LIPID RAFTS - A PERSONAL ACCOUNT -- 5. Theories of Equilibrium In homogeneous Fluids -- 6. Critical lipidomics: The consequences of lipid miscibility in biological membranes -- 7. Lateral diffusion in heterogeneous cell membranes -- 8. Mechanical factors affecting the mobility of membrane proteins -- 9. Membrane domains under cellular recycling -- 10. Protein Pattern Formation -- Part 4: Biomembrane Mechanics and Consequences for their Functions -- 11. Biomembrane mechanical properties direct diverse cell functions -- 12. Spontaneous and intrinsic curvature of lipid membranes: back to the origins -- 13. Membrane-mediated interactions -- 14. Simulating protein-mediated membrane remodeling at multiple scales -- 15. Mechanosensitivity of membrane budding and tracking Lionel Foret -- 16. Common energetic and mechanical features of membrane fusion and fission machineries -- 17. Interaction of particles and pathogens with biological membranes -- 18. Adhesion of biological membranes -- 19. Spatial and mechanical aspects of signal transduction in the cell membrane -- 20. Protein-Induced morphological deformations of biomembranes -- 21. Fluctuations in active membranes.
Biomedical and Life Sciences
text file PDF
Keywords: Biochemistry; Cell membranes .; Biophysics; Biological physics